Question about Bagatrix Algebra Solved! 2005 (105101) for PC

4x+8y=20 || /4

x+2y=5

x=5-2y

-4x+2y=-30 || /2

-2x+y=-15

-2(5-2y)+y=-15

-10+4y+y=-15

5y=-5

y=-1

x=5-2y || y=-1

x=5-2(-1)

x=5+2

x=7

Posted on Mar 10, 2009

This is best written as two separate equations:

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

**y **= -74.75/7.75 =** -9.645161**

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

**x** **=.741935**

8x+3y = -23 and 34x+ 5y = -23

Solving the first one for x:

8x = -23-3y

x = -23/8 - 3/8y

Substituting this value for x into the second equation:

34(-23/8 - 3/8y) + 5y = -23

-97.75 - (34)(.375)y + 5y = -23

-97.75 - 12.75y + 5y = -23

-97.75 -7.75y = -23

-7.75y = 97.75-23=74.75

Substitution back into the equation for x:

x = -23/8 - 3/8(-9.645161)

x = -2.875 + 3.616935

Dec 12, 2014 | Bagatrix Algebra Solved! 2005 (105101) for...

If your question is the inverse of 3x / (4x - 1) then

(4x - 1) / 3x

If you meant (3x / 4x) - 1 then

- 4

(4x - 1) / 3x

If you meant (3x / 4x) - 1 then

- 4

Jun 26, 2014 | SoftMath Algebrator - Algebra Homework...

Do you have a question about this equation?

Mar 19, 2013 | SoftMath Algebrator - Algebra Homework...

=>2x+3=0 ; taken x as common and 4-2=2 i.e. x(4-2) = 2x

=>2x=-3 ; +3's moved on the right-hand side, so it becomes -3

=>x=-3/2 ; 2 has been moved to the right-hand side and divided with -3 i.e 1/2 multiplied by -3 = -3/2

Good luck.

Thanks for using

Aug 13, 2010 | SoftMath Algebrator - Algebra Homework...

Hello,

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

You have the method: apply it.

2 *(3x-4)(4x+5) =(6x-8)(4x+5)

Now apply the FOIL method

F: 6x*4x=24x^2

O: 6x*5=30x

I; -8*4x=-32x

L: -8*5=-40

so the result is

24x^2 + 30x-32x -40 =24x^2 -2x-40

Oct 01, 2009 | The Learning Company Achieve! Math &...

Hello,

You are talking of the distributivity of multiplication with respect to the addition or subtraction. The only term where you have multiplication and addition/subtraction is the one with parentheses because

4(5-6y) = 4*(5-6y). * means multiply by

Distributing the product consists in removing CORRECTLY the parentheses.

I consider the term alone

4*(5-6y) = 4*5 +4*(-6y)= 20 -4*6*y = 20 -24*y

You put this result in a package and replace it where it was it the original expression.

So

8*y -(package) +20= Replace package

8*y -(20-24*y)+20 = 8*y -20 -(-24y) + 20 Remember -*(-) = +

8*y -20 +24*y +20= Remember -20+20 =0

8*y -20 +20 +24*y= Addition is commutative

8*y +24*y = 32*y

Let y be an orange 8 oranges + 24 oranges =32 oranges.Coclusion

**8y-4(5-8y)+20 = 32y**

You are talking of the distributivity of multiplication with respect to the addition or subtraction. The only term where you have multiplication and addition/subtraction is the one with parentheses because

4(5-6y) = 4*(5-6y). * means multiply by

Distributing the product consists in removing CORRECTLY the parentheses.

I consider the term alone

4*(5-6y) = 4*5 +4*(-6y)= 20 -4*6*y = 20 -24*y

You put this result in a package and replace it where it was it the original expression.

So

8*y -(package) +20= Replace package

8*y -(20-24*y)+20 = 8*y -20 -(-24y) + 20 Remember -*(-) = +

8*y -20 +24*y +20= Remember -20+20 =0

8*y -20 +20 +24*y= Addition is commutative

8*y +24*y = 32*y

Let y be an orange 8 oranges + 24 oranges =32 oranges.Coclusion

Sep 10, 2009 | The Learning Company Achieve! Math &...

sec^4X- sec^2X = 1/cot^4X + 1/cot^2X

RHS

1/cot^4X + 1/cot^2X

=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)

=Sin^4X/Cos^4X + Sin^2X/Cos^2X

=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X

=Sin^2X/Cos^4(Sin^2X + Cos^2X)

=Sin^2X/Cos^4X

=(1-Cos^2X)/Cos^4X

=1/Cos^4X - Cos^2X/Cos^4X

=1/Cos^4X - 1/Cos^2X

=Sec^4X - Sec^2X

=LHS

RHS

1/cot^4X + 1/cot^2X

=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)

=Sin^4X/Cos^4X + Sin^2X/Cos^2X

=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X

=Sin^2X/Cos^4(Sin^2X + Cos^2X)

=Sin^2X/Cos^4X

=(1-Cos^2X)/Cos^4X

=1/Cos^4X - Cos^2X/Cos^4X

=1/Cos^4X - 1/Cos^2X

=Sec^4X - Sec^2X

=LHS

Feb 02, 2009 | Super Tutor Trigonometry (ESDTRIG) for PC

x=7

y=-1

y=-1

Jan 30, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

V (2,0) and Focus (2,2)

since the focus is 2 units above the vertex, the parabola opens upward

vertex (h,k)

a is the focal length (distance between the vertex and the focus)

a = 2

(2 units above the vertex)

(x-h)^2 = 4a (y-k)

(x-2)^2 = 4(2) (y-0)

x^2 - 4x + 4 = 8 (y)

x^2 - 4x + 4 = 8y

x^2 - 4x - 8y + 4 = 0

**Answer: "(x-2)^2 = 8 (y)" or in expanded form "x^2 - 4x - 8y +4"

since the focus is 2 units above the vertex, the parabola opens upward

vertex (h,k)

a is the focal length (distance between the vertex and the focus)

a = 2

(2 units above the vertex)

(x-h)^2 = 4a (y-k)

(x-2)^2 = 4(2) (y-0)

x^2 - 4x + 4 = 8 (y)

x^2 - 4x + 4 = 8y

x^2 - 4x - 8y + 4 = 0

**Answer: "(x-2)^2 = 8 (y)" or in expanded form "x^2 - 4x - 8y +4"

Nov 18, 2008 | Super Tutor Trigonometry (ESDTRIG) for PC

Nov 22, 2013 | Bagatrix Algebra Solved! 2005 (105101) for...

352 people viewed this question

Usually answered in minutes!

4x+8y=20

-4x+2y=-30

2x-8y=20

×